Kontestasi Kepentingan dalam Tata Kelola Performing Rights: Polarisasi AKSI dan VISI di Industri Musik Indonesia (2022–2025) - Alana Maria (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
Digital transformation has reshaped the music industry while simultaneously complicating the governance of economic value distribution, particularly regarding performing rights. This article analyzes the polarization between Asosiasi Komposer Seluruh Indonesia (AKSI) and Vibrasi Suara Indonesia (VISI) as a form of political-economic contestation in the governance of music copyright in Indonesia during the 2022–2025 period. Using a qualitative document analysis approach, this study combines Wallis’ (2004) music industry value chain framework with Sabatier and Jenkins-Smith’s (2009) Advocacy Coalition Framework (ACF). Wallis’ framework is used to explain the different structural positions of songwriters and performers within the music industry value chain, while ACF is employed to understand how these competing interests evolved into advocacy coalitions contesting policy direction within the copyright subsystem. The study identifies three main findings. First, the conflict over performing rights reflects the different structural positions of songwriters and performers within the music industry value chain, resulting in competing economic interests regarding control, royalty distribution, and the commercial use of musical works. Second, regulatory ambiguities between Articles 9 and 23 of Indonesia’s Copyright Law No. 28/2014, combined with weak transparency and legitimacy of the National Collective Management Organization (Lembaga Manajemen Kolektif Nasional, LMKN), intensified these tensions and pushed the conflict into the public sphere. Third, individual disputes among musicians eventually evolved into broader collective political mobilization through the establishment of AKSI and VISI, both of which actively engaged in litigation, political lobbying, and intervention in copyright law reform debates, transforming performing rights into a broader struggle over authority in governing Indonesia’s music industry. This article concludes that reforming performing rights governance is essential to ensuring legal certainty, more accountable royalty distribution, and a fairer balance of economic rights protection between songwriters and performers.Theoretically, this study contributes to the Advocacy Coalition Framework (ACF) literature by demonstrating its applicability in analyzing policy contestation within the creative industry sector in developing countries, particularly in contexts where regulatory ambiguity and weak intermediary institutions serve as catalysts for the emergence of new advocacy coalitions.